A Microscopy Study of PVD Grown Cu: Sample preparation, optimisation and in-situ analysis - CANAVAN, MEGAN (Trinity College Dublin. School of Physics. Discipline of Physics, 2019)
A variety of sample preparation techniques have been developed and optimised for PVD grown Cu films and Cu NWs. These techniques include traditional cross-sectional preparation, plan-view preparation, site-specific cross-sectional preparation and in-situ lamella fabrication technique for in-situ annealing within the TEM. These techniques have been developed to obtain high-resolution S/TEM imaging and analysis of Cu film and NW microstructure. Cross-sectional lamellae of 40 nm Cu film on SiO2 were successfully prepared through low kV FIB milling and the employment of an established wedge technique. HRTEM and STEM imaging of these lamellae determined the various grain and grain boundaries present within the Cu film. TEM imaging was performed at both 300 and 80 kV due to the damage experienced by the Cu film at higher accelerating voltages. This was determined to be due to the fact that the evaporated Cu film was of poorer quality to the sputtered 50 nm Cu film on 7 nm Ta later analysed. Cross-sectional lamellae of 50 nm Cu on 7 nm Ta were successfully prepared to a very high quality with minimal damage, uniform crystallinity and little amorphisation. From this high-resolution aberration-corrected STEM imaging and analysis was achieved. Atomic resolution imaging of the Cu film revealed a complex grain boundary mixture of tilt and twist and twin boundaries running at an angle and also parallel to the film surface. Slight misalignments of 1 - 2° within these parallel twin boundaries could potentially be contributing to the out-of-plane rotation of grain boundaries on the film surface detected by STM analysis and simulations. EELS obtained were used to determine the absolute thickness of lamellae with approximate values of 30 nm. Plan-view lamellae of 50 nm Cu film on 7 nm Ta were successfully prepared through various alternative techniques including side-mounted low kV milling, HF etching of the Si substrate to remove the Cu film and in-situ XeF2 etch with the FIB to remove the Si substrate. HRTEM imaging of these lamellae was obtained and the grain size, misorientation angle and texture was analysed through TKD. This confirmed the predominant surface grain orientation being [111] corroborating STM analysis. Site-specific lamellae of Cu NWs were prepared using low kV FIB milling. High-resolution S/TEM imaging of these Cu NWs was achieved. Similar grain boundary features were discovered within these NWs including twin boundaries. Finally, in order to achieve real-time observation of Cu3Si mounds formed during annealing of the 50 nm Cu film on 7 nm Ta, an alternative in-situ lift-out procedure using FIB milling was developed and optimised for the preparation of lamellae for in-situ annealing in the TEM. This technique combined for the first time the use of rotating microgrippers for lift-out and thinning, and a unique adhesive substance, SEMGlu, during the lift-out procedure, instead of the traditional micromanipulator needle and Pt weld. Lamellae were successfully mounted onto a MEMS device for in-situ TEM annealing experiments without damage to the MEMS. HRTEM imaging of the polished lamella verified that this method can produce high quality lamellae comparable with regular in-situ lift-out procedures.
APPROVED
Keywords: Focused Ion Beam; Lamella Preparation; TEM Sample Preparation; Lamella Lift-out